Noble gases in conventional and unconventional petroleum systems - Byrne, D; Barry, P; Lawson, M; Ballentine, C (Geological Society of London, 2017)
Petroleum systems represent complex multiphase subsurface environments. The properties of the noble gases as conservative physical tracers allow them to be used to gain insight into the physical behaviour occurring within hydrocarbon systems. This can be used to better understand the mechanisms of hydrocarbon migration, residence time of fluids, and measurement of the scale of the subsurface fluid system involved in the transport and trapping of the hydrocarbon phase. The noble gases in the subsurface derive from different sources with distinct isotopic compositions, allowing them to be resolved in any crustal fluid. We discuss the processes within petroleum systems that incorporate the noble gases from each of these sources into hydrocarbon accumulations. The dominant mechanism controlling the introduction of air-derived noble gases into petroleum systems is via subsurface groundwater, and this records key information about the interaction of the petroleum system with the hydrogeological regime. Radiogenic noble gases accumulate over time, recording information about the age and relative timing of processes within the petroleum system. We review the conceptual framework and quantitative models describing these processes using examples from previous studies, and discuss both their current limitations and the potential for their application to unconventional hydrocarbon systems.